Delivering sustainable building strategies in Malaysia: stakeholders' barriers and aspirations - Shari, Zalina; Sobarto, Veronica (Faculty of Design & Architecture, Universiti Putra Malaysia, 2012)
In Malaysia there is both top-down and bottom-up pressure to deliver a sustainable built environment. However, most new projects display few sustainability features, explaining the continuous presence of, and increasing problems related to, the environment in Malaysia. This paper presents nine categories of barriers and four categories of measures to overcome the barriers and to promote sustainable building practices, drawn from qualitative research undertaken with thirty Malaysian building stakeholders via in-depth, semi-structured interviews. The primary barriers that were identified by the stakeholders are: 1) a lack of expressed interest in the clients’ requirements; 2) a lack of political will, legislation and enforcement; 3) a lack of technical understanding among project team members; 4) a lack of consideration of sustainability measures by project team members; and 5) real and perceived costs. Whilst measures suggested by the stakeholders are related to the government and regulatory stakeholders, research and education sector, private sector, and clients of the construction industry. The paper concludes that regional characteristics need to be reflected in any sustainability assessment methodologies in order to encourage sustainable development locally